Virtual Reality as an Educational Tool for Elementary School - Figueiredo, M.; Rovilson Mafalda; Andrea Kamensky (Proceedings of IDEAS 2019, 2020)
The new information and communication technologies (ICTs), through virtual and augmented realities, present themselves as innovative and useful digital tools in many different areas. The educational scenario, in the current context of a constant and ever-changing world, requires a pedagogical approach in constant transformation and innovation within the digital culture. This research will present an overview on the stage of VR current apps and educational relation with them and propose the beginning of adoption of this technology on classes as part of a work that seeks to create a social innovation experiment with public school teachers for the newly created “Media-Education” discipline in order to disseminate virtual reality and 360° camera knowledge and applications, as well as to understand how schools and educators are up to date and are positioning themselves in front of the new technologies. It is mandatory to be updated on the new apps and technologies and create new approaches where virtual reality can be a useful tool.